FMADM for determining superior commodity at agroindustry area - Mulawarman, Aditya; Sudrajat, Ajat; Hendri, Nedi; Kamar, Karnawi; Mulyadi, Dedi; Budiyanto, Gunawan; Huda, Miftachul; Abdul Latif, Aliza; Maseleno, Andino (International Journal of Engineering and Technology, 2018)
Indonesia has many excellent commodities that are spread throughout Indonesia, especially in Lampung province. Lampung Province has excellent commodities, among others: coffee, rubber, oil palm, cocoa and coconut. To determine the superior commodity in Lampung province, a decision support model is needed to determine the superior commodities in the agroindustry. This study aimed to create a decision support model that can facilitate in determining the suitable and feasible priority of superior in agroindustry. The commodity is to be developed. The research was carried out by designing application that was developed by using computer programming language and applying the principle of system development by applying the best alternative decision-making method from certain criteria, namely Fuzzy Multiple Attribute Decision Making (FMADM). Fuzzy MADM is a method used to find optimal alternatives from a number of alternatives with certain criteria. This method was chosen because this method determines the weight for each attribute, followed by an alternative rating that will determine the superior commodity for agroindustry in Lampung Province based on the calculated weight using fuzzy formula to get more accurate results about the superior commodity in Lampung province.Â Â Â Â Â Â Â